Benthic organic carbon release stimulates bacterioplankton production in a clear-water subarctic lake - Rodriguez, Patricia Laura (2013)
We carried out a set of experiments in a small clear-water lake in northern Sweden during summer 2010 to assess the effect of organic C (OC) released from epipelic algae on pelagic bacterial production (BP). The release rate of OC (dissolved and particulate) from epipelic algae was ,45.4 ng C m22 h21 . Bacterioplankton uptake of dissolved OC was P-limited, and pelagic primary production (PP) was colimited by N and P. Pelagic BP (3.2 6 6 mgCL21 h21 ) exceeded pelagic PP (0.012 6 0.008 mg C L21 h21 ). Pelagic BP was higher in lake water in contact with sediments and the epipelic algae growing on their surface than in water separated from the sediments. Epipelic algae release OC to lake water and potentially stimulate pelagic BP. However, exploitation of benthic OC probably is suboptimal because of nutrient limitation (primarily by inorganic P) of BP.